2018
DOI: 10.1088/1367-2630/aab5c7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of external potential for field emission resonances and its applications on nanometer-scale measurements

Abstract: The form of the external potential (FEP) for generating field emission resonance (FER) in a scanning tunneling microscopy (STM) junction is usually assumed to be triangular. We demonstrate that this assumption can be examined using a plot that can characterize FEP. The plot is FER energies versus the corresponding distances between the tip and sample. Through this energy-distance relationship, we discover that the FEP is nearly triangular for a blunt STM tip. However, the assumption of a triangular potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Recent studies have explained that under the same current, more FERs result from a sharper STM tip. [22][23][24] Fig. 1(b) also shows that the higher-order peaks in the spectra with three and ve FERs are all much narrower than those in the spectra with four and six FERs.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Recent studies have explained that under the same current, more FERs result from a sharper STM tip. [22][23][24] Fig. 1(b) also shows that the higher-order peaks in the spectra with three and ve FERs are all much narrower than those in the spectra with four and six FERs.…”
Section: Resultsmentioning
confidence: 89%
“…S2 †). 34 On the contrary, the linewidth modulation vanishes on Ag(111) without a band gap above the vacuum level (see ESI note 3, Fig 24 According to electrostatics, the electric eld in an STM junction is not constant due to the tip structure similar to that in This journal is © The Royal Society of Chemistry 2020…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our measurement results and the obtained theoretical model describe the same behavior. Therefore, it can be stated that the probability density of the field-emission current is accurately modeled by ( 7), (8), and (10).…”
Section: B Modeling Of the Mean And Variancementioning
confidence: 99%
“…Consequently, FER has been a versatile technique to explore various phenomena . For example, the FER number can reflect the sharpness of an STM tip; a higher FER number indicates a sharper tip [17,35,36]. In addition, previous studies demonstrated that the FER observed on the reconstructed surfaces revealed spatial variation in linewidth [32][33][34].…”
Section: Introductionmentioning
confidence: 99%